2017
DOI: 10.1038/ijo.2017.149
|View full text |Cite
|
Sign up to set email alerts
|

Antrodia cinnamomea reduces obesity and modulates the gut microbiota in high-fat diet-fed mice

Abstract: Background:Obesity is associated with gut microbiota dysbiosis, disrupted intestinal barrier and chronic inflammation. Given the high and increasing prevalence of obesity worldwide, anti-obesity treatments that are safe, effective and widely available would be beneficial. We examined whether the medicinal mushroom Antrodia cinnamomea may reduce obesity in mice fed with a high-fat diet (HFD).Methods:Male C57BL/6J mice were fed a HFD for 8 weeks to induce obesity and chronic inflammation. The mice were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 62 publications
8
72
1
Order By: Relevance
“…It is no surprise that our results are similar to previous studies [17,[28][29][30][31] showing that both CO and TC efficiently controlled impaired glucose metabolism and improved hyperglycemia. However, our results are inconsistent with previous studies in that TC did not inhibit weight gain or reduce lipid accumulation [28][29][30]. This might be due to the longer-term high-fat diet induction experiment (HFD for 24 weeks) in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is no surprise that our results are similar to previous studies [17,[28][29][30][31] showing that both CO and TC efficiently controlled impaired glucose metabolism and improved hyperglycemia. However, our results are inconsistent with previous studies in that TC did not inhibit weight gain or reduce lipid accumulation [28][29][30]. This might be due to the longer-term high-fat diet induction experiment (HFD for 24 weeks) in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that TC can reduce obesity and attenuate hyperglycemia in rodents, and may act by regulating the composition of the gut microbiota [28][29][30]. It has also been confirmed that CO inhibits hyperlipidemia and hyperglycemia [17,31].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Akkermanisia could reduce chronic inflammation and restore intestinal barrier function in murine model, indicating a correlation between the abundance of Akkermansia and the degree of inflammation . Also, it was found that increased abundance of Akkermanais co‐occurred with partial protection against inflammation in mice fed A. cinnamomea water extract . Furthermore, recent studies showed that sulfate‐reducing bacteria, including Desulfovibrionaceae , were potential endotoxin producers leading to low grade and chronic inflammation .…”
Section: Discussionmentioning
confidence: 96%
“…Emerging evidence has shown that colitis can promote colon carcinogenesis by altering the composition of gut microbiota, impairing barrier function and facilitating the expansion of bacteria with genotoxic capability . Targeting the gut microbiota with prebiotic mushrooms ( Ganoderma lucidum and Antrodia cinnamomea ) has been shown to produce beneficial effects on diet‐induced obesity and low‐grade inflammation . Certain prebiotic components of mushrooms such as glucans have also been reported to be anti‐inflammatory in the colon .…”
Section: Introductionmentioning
confidence: 99%